KINA: Application of ecocentrism based learning to strengthen early forest care spirit through the tri hita karana value approach - Siregar, Esterlina Br; Habsyi, Muhammad Harun Rasyid Al; Hasan, M Khoirul (Journal of Environment and Geography Education, 2025)
Background: The transition from Gen Z to Gen Alpha has led to a shift in social activities, with children facing challenges from excessive device use, resulting in potential addiction and exposure to negative content. This issue is often rooted in inaccurate parenting methods. To address this, the value of Tri Hita Karana, which promotes harmony between humans, nature, and God, offers a potential solution. The KINA game application aims to mitigate these issues by incorporating this ancestral value while fostering climate action and forest awareness. Method: The study adopts a performance testing method with qualitative data quantification using scoring. The KINA game application integrates Ecocentrism Based Learning (EBL) within a pedagogical curriculum and utilizes User Interface (UI) and User Experience (UX) technology tailored for Gen Alpha. The implementation approach focuses on evaluating the effectiveness of the application in promoting climate action and forest awareness. Findings: The KINA game application successfully integrates the principles of Tri Hita Karana and Ecocentrism Based Learning (EBL), helping children develop an early awareness of environmental sustainability. The application demonstrates the potential to reduce device addiction while fostering a positive shift in social behavior among children, aligning with SDGs goals 4 (Quality Education), 13 (Climate Action), and 15 (Life on Land). Conclusion: The KINA application effectively addresses issues of device addiction and negative content exposure in children by promoting climate action and forest awareness. By integrating Ecocentrism Based Learning and Tri Hita Karana values, KINA offers a sustainable and educational solution to foster environmental consciousness from an early age. Novelty/Originality of this article: The KINA game application uniquely combines Ecocentrism Based Learning, Tri Hita Karana, and pedagogical curriculum design to educate children on climate action and forest awareness, offering a novel approach to parenting and digital education for the Alpha Generation.